2017
DOI: 10.3389/fpls.2017.01334
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Aquaporin Transport System in Eelgrass (Zostera marina L.), an Aquatic Plant Species

Abstract: Aquaporins (AQPs) are a class of integral membrane proteins involved in the transport of water and many other small solutes. The AQPs have been extensively studied in many land species obtaining water and nutrients from the soil, but their distribution and evolution have never been investigated in aquatic plant species, where solute assimilation is mostly through the leaves. In this regard, identification of AQPs in the genome of Zostera marina L. (eelgrass), an aquatic ecological model species could reveal im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Recently, Ma et al [68] have shown that Si supply under Cd stress in rice upregulated the expression of OsLsi1 (encoding for Si transport NIP-III (Nodulin 26-like intrinsic proteins-III) Aquaporin) and downregulated the expression of Nramp5 , a gene involved in the Cd transport. However, many plant species particularly belonging to family brassicaceae [69], solanaceae [70], and Linaceae [71] does not carry any Si-transporter (NIP-III Aquaporin) and are known as poor Si accumulators. However, several reports suggesting Si derived benefits in such species make it more difficult to understand the molecular consequences [72,73].…”
Section: Silicon-mediated Mechanisms Of Metal Detoxificationmentioning
confidence: 99%
“…Recently, Ma et al [68] have shown that Si supply under Cd stress in rice upregulated the expression of OsLsi1 (encoding for Si transport NIP-III (Nodulin 26-like intrinsic proteins-III) Aquaporin) and downregulated the expression of Nramp5 , a gene involved in the Cd transport. However, many plant species particularly belonging to family brassicaceae [69], solanaceae [70], and Linaceae [71] does not carry any Si-transporter (NIP-III Aquaporin) and are known as poor Si accumulators. However, several reports suggesting Si derived benefits in such species make it more difficult to understand the molecular consequences [72,73].…”
Section: Silicon-mediated Mechanisms Of Metal Detoxificationmentioning
confidence: 99%
“…Variation in the number of AQP subfamilies specific to different plant species has been reported. Among the five subfamilies, XIPs are absent entirely from monocots and dicots like Brassicaceae [ 9 11 ]. In primitive land plants, two additional unique classes of AQPs, GlpF-like intrinsic protein (GIPs) and hybrid intrinsic proteins (HIPs) have been described and are presumed to have been lost in the course of evolution [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the seed plants, variation was observed in the distribution of five subfamilies. The entire monocot clade, as well as some dicot families such as the Brassicaceae, have lost the entire XIPs lineage [ 1 , 15 , 50 ]. The absence of the XIPs in rice and Arabidopsis, the two extensively studied model plants, limits the efforts to characterize the functions of XIPs when compared to other subfamilies.…”
Section: Discussionmentioning
confidence: 99%